Investigation of a buckled beam generator with elastic clamp boundary. (27th October 2016) - Liu, Weiqun; Formosa, Fabien; Badel, Adrien; Agbossou, Amen; Hu, Guangdi
Abstract: A compact nonlinear bistable oscillator (NLBO) based on a double buckled beams and a concentrated mass is proposed and studied considering elastic boundary conditions. A unified analytical model including different elastic conditions is derived. Comparative modal analysis studies of the model and a finite element approach present consistent results. Good agreements with experiments results further validate the effectiveness of the model. It is shown that the proposed NLBO overcomes the band limitation of the regular linear oscillators and possesses a good capability of wide bandwidth for different applications. The proposed investigations suggest that the elastic clamp boundary can enhance the NLBO's performance with proper arrangements. A feasible solution of modifying the axial stiffness to tune the desired energy potential shape and keeping the beam parameter unvaried simultaneously is then available. It provides additional options of design and optimization to break the restriction of fabrication or other issues.